The Effects of Solvent Polarity on Hypoglycemic and Hypolipidemic Activities of Securigera Securidaca (L.) Seeds - Ahmadi, A.; Khalili, M.; Margedari, Sh.; Nahri-Niknafs, B. (Drug Research, 2016)
The search for indigenous natural antidiabetic and antilipidemec agents is still ongoing. Medicinal plants are widely used for this purpose. These herbs are very rich sources of bioactive compounds as flavonoids, polyphenols, tannins, alkaloids which have been reported as effective role to reduce blood glucose and lipid levels. Securigera securidaca seed is reputed in folk medicine for their value as antidiabetic and antilipidemec drugs. In this research, the effect of solvent polarity in bioactive extraction contents of this plant was evaluated by GC-MS analysis. Then antidiabetic and antilipidemic activies of different extracts were investigated in streptozotocine-induced diabetic rats and compared to glibenclamide as known chemical drug for diabetes.The results indicated that, carbon tetrachloride extract of Securigera securidaca seeds showed the best and significant hypoglycemic and hypolipidemic activities compared to other extracts because of its more sterols and fatty acids content with beta cells protecting effect from high glucose-induced apoptosis and also increasing in insulin level and sensitivity.
Keywords: solvent polarity; securigera securidaca seeds; blood glucose and lipid levels; streptozotocine-induced diabetic rats; sterols and fatty acids